Muscularity rationality: An examination of the use of Rational Emotive Behaviour Therapy (REBT) upon exercisers at risk of muscle dysmorphia. (January 2021) - Outar, L.; Turner, M.J.; Wood, A.G.; O'Connor, H.
Abstract: Research in the area of body image suggests that muscularity dissatisfaction is a prominent concern among men and women. At its apex, this concern manifests into a convoluted and debilitating body image disorder termed muscle dysmorphia (MD), characterised by a marked preoccupation with ones (subjective) muscularity and leanness inadequacy. Prevention of MD is critical, however, empirical evidence informing intervention protocols are profoundly scarce. The principal aim of this study was to examine the effectiveness of a one-to-one Rational Emotive Behaviour Therapy (REBT) intervention, comprising five, 60-min one-to-one sessions, in decreasing MD symptomatology, irrational beliefs and increasing unconditional self-acceptance in a mixed-sex cohort of four exercisers at-risk of MD. A single-case, staggered multiple-baseline across participant A-B design was adopted to examine the effects of REBT. Visual and statistical analyses, and social validation data, indicated reductions in MD, irrational beliefs, and increases in unconditional self-acceptance across all participants from pre-post intervention phases, with reductions upheld at a 6-month follow-up. This study highlights the potential role of rational and irrational beliefs in the onset and maintenance of MD. This study is the first to report the application of a CBT approach to MD symptomology, and has demonstrated the use of REBT as a potential preventative approach for individuals at risk of MD. Practitioners working with individuals at risk of MD should take a benefit-focussed approach to support individuals in developing unconditional self-acceptance beliefs, as well as a problem-focussed approach to support individuals in reducing irrational beliefs. Highlights: Athletes and exercisers may be at greater risk of developing muscle dysmorphia (MD) symptomology. Rational Emotive Behaviour Therapy brought about reductions in MD symptomology, irrational and rational beliefs from pre-post intervention. MD symptomology, irrational and rational beliefs results, were maintained at a six-month follow up. Practitioners working with those at-risk of MD, should adopt a benefit-focussed approach and develop USA, as well as reducing irrational beliefs.